Muscular and Vascular Fallopian Tube Morphology in Ectopic Tubal Pregnancy - Baxi, Seema; Koyani, Mitesh; Sabugar, Md Hashmi; Pandya, Dhwani (Annals of Pathology and Laboratory Medicine, 2024)
Background Although literature is full of articles on histopathological changes in fallopian tube in ectopic pregnancy and the predisposing conditions associated with ectopic pregnancy, none have mentioned or reported abnormal muscle and vascular architecture of the tube. The study was undertaken to find the percentage of different sites of ectopic pregnancies coming to the institute for treatment and to calculate the proportion of various morphological risk factors which could have led to the ectopic pregnancy and to discern the various histopathological changes in cases of ectopic tubal pregnancies. Methods A retrospective study was conducted on all the cases of ectopic pregnancies in the year of 2021 and 2022. For comparison of morphological changes equal number of tubes received for tubal ligation were assessed as they served age matching purpose. Hematoxylin & eosin-stained slides were retrieved and re-examined for the histological patterns. Results 92% of the ectopic pregnancies were tubal pregnancies. Amongst predisposing factors of tubal pregnancies detected morphologically, chronic salpingitis was seen in 71.5% of cases while Salpingitis Isthmica Nodosa (SIN) was seen in 26.1% of cases. Conclusion Abnormal morphological findings like tubal muscle splaying, arterial wall thickening leading to grotesque shapes, clear changes in different layers of tunica of blood vessel with or without concentric muscle splaying were seen in tubal ectopic pregnancies in significant numbers of cases.